Pengaruh Kepemimpinan Strategis terhadap Kinerja Agen Properti dengan moderasi Motivasi dan Pelatihan - Ester Minarni (JEMAP, 2019)
This research about effect of strategic leadership toward property agent’s performance aimed to know how big was the effect with motivation and training as moderating variabel.  This study was conducted in Hore Property Office in Semarang. Population of this research were all of property agents and purposive sampling was conducted toward 75 respondents who are actively running business. Data collecting technique used survey method with questionnaire. Data analysis technique used descriptive and regression analysis with test of the difference of absolute value to know moderating variable. Research result conducted showed that strategic leadership influenced positively and significantly toward agent’s performance. The motivation and training varibles did not significantly influence as moderating variable. It is suggested that there should be strategic guidance for agents to maintain or increase their performances. Motivating and training effort should be developed with variation of technics and activities so becomes fruitful and hands on skill for agents